2018
DOI: 10.1002/2017jd027498
|View full text |Cite
|
Sign up to set email alerts
|

Comparisons of Ice Water Path in Deep Convective Systems Among Ground‐Based, GOES, and CERES‐MODIS Retrievals

Abstract: Retrievals of convective cloud microphysical properties based on passive satellite imagery are difficult. To help quantify their uncertainties, ice water paths (IWPs) retrieved from the NASA Clouds and the Earth's Radiant Energy System project using Geostationary Operational Environmental Satellite (GOES) and Terra/Aqua MODerate‐resolution Imaging Spectroradiometer observations are compared with IWPs retrieved from Next‐Generation Radar (NEXRAD) observations over a large domain (32°N to 40°N and 105°W to 91°W)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 43 publications
0
9
0
Order By: Relevance
“…The retrieval algorithms are capable of characterizing IWCs over the SR regions of midlatitude continental convective systems. The retrieved IWPs based on radar reflectivity are also used to compare with satellite‐retrieved IWPs to help quantify the uncertainties in the satellite retrievals (Tian et al, ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The retrieval algorithms are capable of characterizing IWCs over the SR regions of midlatitude continental convective systems. The retrieved IWPs based on radar reflectivity are also used to compare with satellite‐retrieved IWPs to help quantify the uncertainties in the satellite retrievals (Tian et al, ).…”
Section: Methodsmentioning
confidence: 99%
“…In this study, most analyses are based on the radar-reflectivity-retrieved products; therefore, a significant amount of uncertainty could be realized during the generalization of the results. The retrieved IWCs for the SR region have been validated in Tian et al (2016Tian et al ( , 2018 and showed uncertainties around 20% to 40% against the in situ measurements. These uncertainties are consistent but smaller when compared to the K dp -retrieved IWCs and IWPs for the SR region.…”
Section: 1029/2019jd030330mentioning
confidence: 99%
“…Ice water paths for deep convective clouds determined from the Next-Generation Radar (NEXRAD) data over the south central United States were compared in [114] with Ed4 Terra and Aqua retrievals and with Ed4-like retrievals from GOES imager data. It was determined that the GOES and Ed4 retrievals underestimated the NEXRAD IWP by 4 ± 61% and 9 ± 59%, respectively, for the thick anvil portions of the convective systems, which had a mean IWP of 2.24 kg•m −2 .…”
Section: Cloud Optical Depth Particle Size and Water Pathmentioning
confidence: 99%
“…For thick convective clouds, the determination of IWP and CWP from any type of sensor is less certain than for thin clouds. In comparisons with NEXRAD retrievals, Tian et al (2018) found that the SatCORPS IWP was, on average, 10% lower than the radar estimates for ice-only anvils. However, in stratiform rain portions of the convection, the IWP underestimate is 20% due to the prevalence of larger ice crystals lower in the cloud and to the SatCORPS optical depth retrieval limit of 150.…”
Section: Satellite-retrieved Productsmentioning
confidence: 87%